Doctrine of consent in criminal law / Huzida Hussein - Hussein, Huzida (Faculty of Law, 1986)
One of the primary aims of Criminal Law is the protection of life and the integrity of the body. In other words, man's life is not being taken away as any way by anybody who wishes to do so. Like a proverb of an Englishman; God gives us life and He's the only one who has the right to take it back. General speaking, a person who kills or injures another is punished and this may extend even to an act which has been consented to. Consent is not a defence to killing, mayhem or abortion. The law however, does not pursue this aim without due consideration being given to individual liberty. Consent may exculpate a person from criminality; if not a doctor can be charged for assault eventhough the patient had consented to the operation. There are certain acts which are lawful despite the need of consent. The right of reasonable chastisement is given to the parents, guardians, masters and school teachers.4 While the scope of the operation of consent is clearly defined in certain areas. But the extent to which it puts an end to the act of criminal is not always clear. Therefore, it is proposed in this paper to consider the rationale of the doctrine of consent and some of the more controversial areas of uncertainty